FRAUD RISK ASSESSMENT: EXPERIMENTAL STUDY ON THE ALTERNATIVE FRAUD MODEL AND AUDITOR RISK PREFERENCES - Artati, Arintyas Kristi; Noviyanti, Suzy (Jurnal Reviu Akuntansi dan Keuangan)
Fraud risk assessment is an important part of the audit process and one of the toughest challenges faced by auditors. In considering fraud risk assessment, fraud models and risk preferences can influence auditor’s decisions. This study uses a 2x2 between-subject experimental design with a total of 110 auditors of public accountant firms in Central Java as participants and produces 60 data ready for processing. Participants were formed into 4 groups with different treatments which the treatments consist of Diamond Fraud model with high and low risk preferences and Pentagon Fraud model with high and low risk preferences. The results show that the use of Pentagon Fraud model will result a more conservative fraud risk assessment. When auditors dare to take high risk action, the resulting fraud risk assessment will be low. In addition, the fraud model and risk preference variables show a significant influence on the performing of fraud risk assessment. There is an interaction between fraud models and auditors’ risk preferences in the performance of fraud risk assessment.